Platelet reactivity and immature platelets in patients with Covid-19. (14th October 2021) - Cohen, A; Harari, E; Cipok, M; Bryk, G; Karp Lador, N; Mann, T; Mayo, A; Lev, E I
Abstract: Background: Coronavirus disease 2019 (Covid-19) is associated with high incidence of thromboembolic events, both venous and arterial. Currently, there are no clinical or laboratory markers to guide antithrombotic therapy in COVID-19 patients. Immature platelets represent a population of hyper-reactive platelets associated with arterial thrombotic events. Objectives: To determine indices of immature platelets and platelet reactivity in Covid-19 patients. Methods: This prospective study compared consecutive COVID-19 patients (n=47, median age = 56 years) to patients with acute myocardial infarction (AMI, n=100, median age = 59 years) and a group of stable patients with cardiovascular risk factors (n=64, median age=68 years). Immature platelet fraction (IPF) and immature platelet count (IPC) were determined by the Sysmex XN-3000 auto-analyzer on admission and at subsequent time-points. Results: IPF% on admission was higher in the Covid-19 group than the stable group and similar to the AMI group (4.8% [IQR 3.4–6.9], 3.5% [2.7–5.1], 4.55% [3.0–6.75], respectively, p=0.005 for Covid-19 vs. stable). IPC on admission was also higher in the Covid-19 group than the stable group and similar to the AMI group (10.8×10 9 /L [8.3–18.1], 7.35×10 9 /L [5.3–10.5], 10.7×10 9 /L [7.7–16.8], respectively, P<0.0001 for Covid-19 vs. stable). The maximal IPF% among the Covid-19 group was higher than the stable group and similar to the AMI group. The maximal IPC in the Covid-19 group was higher than the maximal IPC in both the stable and AMI groups (Covid-19: 14.4×10 9 /L [9.4–20.9], AMI: 10.9×10 9 /L [7.6–15.2], P=0.0035, Stable: 7.55×10 9 /L [5.55–10.5], P<0.0001). Conclusions: Patients with Covid-19 have increased immature platelets indices compared to stable patients with cardiovascular risk factors, and as the disease progresses also compared to AMI patients. Enhanced platelet turnover and reactivity may, therefore, have a role in the development of thrombotic events in Covid-19 patients. Funding Acknowledgement: Type of funding sources: None.